Business Model Innovation and Micro and Small Enterprises’ Performance in Nigeria: Does Entrepreneurial Orientation Mediate? - Faloye, Olaleye Dotun; Owoeye, Idowu (European Journal of Economics and Business Studies, 2021)
The critical role of business model innovation (BMI) in a firm’s performance has earned increasing attention from scholars and management practitioners in recent years. However, empirical research on how BMI linked business performance is quite skimpy. This study examines the effect of BMI on micro and small enterprises (MSEs) and how entrepreneurship orientation (EO) mediates the relationship. A survey research design is used in this study. Data were obtained from 142 MSEs operating in Ondo State, Nigeria, purposively selected for this study. The results revealed that BMI (? = 0.630; ? -0.01) had a positive and significant influence on the MSEs’ performance. More so, this study found that EO (? = 0.716; ? -0.01) is positively related to a firm’s performance. This study finding revealed a positive and significant link between EO and BMI (? = 0.838; ? = 0.000). Also, this study showed that EO mediates the relationship between BMI and a firm’s performance (EO: ?= 0.5740; BMI: ? = 0.1281; ? -0.05). Statistically, the study’s findings also exhibited that out of the six constructs used to capture BMI, only two constructs, namely, market opportunities (?=0.193; ? -0.01) and increment in revenue generation ((?=0.230; ? -0.01), had positive and significant links with the firm’s performance. This study concluded that MSEs in developing economies, especially in sub-Saharan African countries, should integrate BMI and EO activities into their operations to overcome the macerate performance that characterized the Covid 19 pandemic period.